Gamified Formative Assessment with Quizizz to Enhance Learning Outcomes at Madrasa - Hidayati, Naili; Aripin, Syamsul; Hina, Shahzadi (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study investigates the effectiveness of gamified formative assessment using Quizizz to improve learning outcomes at a madrasah. Formative evaluation is essential to support learning engagement and achievement. This qualitative research employed a case study approach involving Grade 7 students and subject teachers. Data were collected through semi-structured interviews and classroom observations, then analyzed using the Miles and Huberman interactive model. The findings indicate that Quizizz enhances student motivation and engagement, with 85% of learners reporting increased enthusiasm in classroom activities. Moreover, the average test scores improved from 70 to 82 following its implementation. While Quizizz provides advantages such as real-time feedback and interactive features, challenges such as limited internet access and inadequate devices remain. The study recommends integrating gamified tools like Quizizz into the curriculum and providing teacher training to optimize digital-based learning. Penelitian ini mengkaji efektivitas asesmen formatif berbasis gamifikasi menggunakan Quizizz dalam meningkatkan hasil belajar di sebuah madrasah. Evaluasi formatif penting untuk mendukung keterlibatan dan pencapaian belajar siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus yang melibatkan siswa kelas VII dan guru mata pelajaran. Data dikumpulkan melalui wawancara semi-terstruktur dan observasi kelas, kemudian dianalisis dengan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa penggunaan Quizizz meningkatkan motivasi dan keterlibatan siswa, dengan 85% siswa melaporkan antusiasme belajar yang meningkat. Selain itu, nilai rata-rata tes meningkat dari 70 menjadi 82 setelah implementasi aplikasi ini. Meskipun menawarkan keunggulan seperti umpan balik instan dan fitur interaktif, tantangan seperti keterbatasan akses internet dan perangkat masih ditemukan. Studi ini merekomendasikan integrasi alat gamifikasi seperti Quizizz dalam kurikulum serta pelatihan guru untuk mengoptimalkan pembelajaran berbasis digital.